Hubungan Perilaku Merokok, Aktivitas Fisik, Obesitas Sentral dengan Kejadian Hipertensi pada Polisi Perokok Di Polsek Tugu, Kota Semarang - Shinta Furry; Dwi Hartanti; Mohammad Arifin (Media Gizi Ilmiah Indonesia, 2024)
Hypertension is a silent killer whose causes and symptoms are unknown. Occupational factors such as police have a risk for hypertension. Most police have poor habits in maintaining health and performance in carrying out their duties. The habit of smoking, sedentary and eating foods that are fatty and high in sodium can cause the onset of cardiovascular diseases. The purpose of this study was to determine the relationship between smoking behavior, physical activity and central obesity with the incidence of hypertension in smoking police at the Tugu Police Station, Semarang City. The study was conducted with a cross sectional design. The total sample in this study was 35 respondents. The data retrieval technique uses total sampling. Data collection using smoking behavior questionnaires to determine the amount, duration and type of cigarettes consumed. Physical activity using the International Physical Activity Questionnaire (IPAQ). Central obesity using a metlin tape and hypertension using a digital sphygmomanometer. Data analysis using Mann-Whitney tests and ordinal logistic regression tests. Mann-Whitney test results on smoking behavior between the number of cigarettes with hypertension (p = 0.037), smoking duration with hypertension (p = 0.020) and cigarette type with hypertension (p = 0.015), Mann-Whitney test results on physical activity with hypertension (p = 0.001) and Mann-Whitney test results of central obesity with hypertension (p = 0.003). As well as the smoking behavior and physical activity variable that most influences the incidence of hypertension